Penerapan Metode Bercerita Menggunakan Media Audio-Visual untuk Meningkatkan Pemahaman Anak Usia Dini Mengenai Bencana Alam - Dwinta Putri, Anak Agung Ayu (Universitas Pendidikan Ganesha, 2019)
This study aimed to examine the influence of the storytelling method use audio-visual media toward children’s comprehension about nature disaster at Group B of Gugus V Kindergarten's of Sukawati at an academic year of 2018/2019. This study was quasi-experiment with nonequivalent control group design and used a quantitative study approach. Populasi of this study was all of Group B of Gugus V Kindergarten's in Sukawati district, which contained 268 children. Group B1 Wirya Kumara Kindergarten was chosen as an experiment group and group B3 Candra Kumara Kindergarten as a control group. Children’s comprehension data collected with the non-test instruments through observation. Collected data analysts use the T-test. Based on analyzing data obtained tcount 2,38 with 5% of significance (dk 47), ttable 2,021. The calculation means that tcount > ttable (2,38>2,021) therefor there was a significant differentiation of children’s comprehension about a natural disaster between the experiments group and the control group. From the analysis, the average value of children's comprehension about a natural disaster in the experiment group was 91,19 which is bigger than the control group with 88,81. The conclusion of this study was the learning process in which the storytelling method and audiovisual media were included was significantly influences children’s comprehension of a natural disaster.